Gen Z Political Participation in the 2024 Simultaneous Elections - Agus Mulyono (Jurnal Info Sains : Informatika dan Sains, 2024)
This research aims to find out how Generation-Z's political participation will be in facing the simultaneous general election agenda in 2024. This research uses a qualitative-descriptive research method, and the results of this research explain that Generation-Z's political participation in general elections is an important thing that cannot be denied by election organizers or election participants themselves. The increase in voter participation is in line with people's understanding of exercising their right to vote, such as generation Z as first-time voters. Strengthening political participation plays a central role in increasing Generation Z's understanding and involvement in simultaneous general election contestations. In fact, Generation-Z's political participation is a real manifestation of a person's or citizen's involvement in electing state leaders, and directly or indirectly influencing government/state policy. Generation Z's inclusive political participation will also bring long-term benefits to Indonesian democracy, by involving them from an early age and providing positive participation experiences, we can form a generation of voters who are educated, informed and trained in making intelligent political decisions. This will strengthen the foundations of our democracy, create a more inclusive political climate, and build strong political awareness among Generation Z.